Visualization of network information devices - Lightweight Directory Access Protocol (LDAP) directory as network information service / Rafidah Zakaria - Zakaria, Rafidah (2013)
Lightweight Directory Access Protocol or LDAP is an Internet protocol that email and other programs use to look up information from a server. It is not limited to contact information or even information about people. LDAP is used to look up encryption certificates, pointers to printers and other services on a network. LDAP is appropriate for any kind of directory-like information, where fast lookups and less frequent updates are the norm. As the number of different networks and applications has been increasing, the number of specialized directories of information also has been increasing causing in over loaded of information that is hard to share and manage. Hence, for this case we create Lightweight Directory Access Protocol (LDAP) directory to retain and retrieve all of this information of network devices (device name, IP address, type and category) in a constant and controlled manner. In order to get the information of network devices, OpManager software will be used to capture the information of network devices. When the information of the network device has been captured, the information will be sync to the LDAP directory created and the information will be visualized through a webpage created using Dreamweaver software.